The mental-psychonetic complex as an integral conceptual model - Olena Kresan; Кресан Олена; Kresan Olena; Svitlana Shchur; Щур Світлана; Shchur Svitlana (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The article focuses on the problems of conceptual modelling, which during the last decades was used in cognitive linguistics on the basis of the frame model (a cognitive model that structures mental spaces), linguistic networks, schemes, prototypes and gestalts. In the field of cognitive onomasiology, the Ukrainian researcher OlenaSelivanova proposed a new type of conceptual model. It is known as a mental-psychonetic complex(MPC)or, in other words, a multi-substrate unit of knowledge that describes the motivational basis of the internal programming of verbal signs. The model of the mental-psychonetic complex was tested by school representatives on the material of nominative classesof various languages, as well as in the analysis of the nominative and cognitive nature of phraseological units of the Ukrainian language and poetic syntax. Conceptual analysis of signs of various types using the mental-psychonetic complex model enabled anew approach to the problem of motivation, development of its new typology, development of non-linear positional schemes of syntactic structures of a non-propositional (metaphorical) nature. The term “psychonetics”was first used by Japanese futurists to describe a post-information society in which efficient data processing operations are valued more than data accumulation. A psychonetic approach to modelling concepts involves a broader view of the problems of cognition and manipulation of concepts. The model covers the interaction of conscious and unconscious mental processes. MPC aims to represent the concept as a dynamic structure consisting of multiple overlapping and interacting layers and planes. Different aspects of consciousness, such as intelligence, emotions, perception, memory and other cognitive functions are combined into a complex that determines the specifics of human behaviour and thinking. The model takes into account that the course of mental processes is influenced not only by individual experience, but also by universal symbols and archetypes that exist in the collective unconscious, which is shared by all people. Thanks to the integration of various aspects of mental activity, individuals develop a higher degree of self-awareness, which significantly increases the efficiency of cognitive data processing.

Резюме. Стаття зосереджена на проблемах концептуального моделювання, яке протягом останніх десятиліть застосовувалосьу когнітивній лінгвістиці на основі фреймової моделі (когнітивної моделі, котра структурує ментальні простори), лінгвальних мереж, а також на основі схем, прототипів і гештальтів. У галузі когнітивної ономасіології українська дослідниця О.Селіванова запропонувала новий тип концептуальної моделі. Він відомий як ментально-психонетичний комплекс чи, іншими словами, мультисубстратна одиниця знання, яка описує мотиваційну базу внутрішнього програмування вербальних знаків. Модель ментально-психонетичного комплексу була апробована представниками школи на матеріалі номінативних класів різних мов, а також при аналізі номінативної й когнітивної природи фразеологізмів української мови та поетичного синтаксису. Концептуальний аналіз знаків різних типів за допомогою моделі ментально-психонетичного комплексу уможливив новий підхід до проблеми мотивації, вироблення її нової типології, розробку нелінійних позиційних схем синтаксичних структур непропозиційної (метафоричної) природи. Термін «психонетика» вперше використали японські футурологи для опису постінформаційного суспільства, в якому ефективні операції обробки даних цінуються вище, ніж накопичення даних. Психонетичний підхід до моделювання понять передбачає більш широкий погляд на проблеми когніції та маніпулювання поняттями. Модель охоплює взаємодію свідомих і позасвідомих психічних процесів. MPC має на меті відобразити концепт як динамічну структуру, що складається з кількох шарів і площин, які перекриваються та взаємодіють. Різні аспекти свідомості, як-то інтелект, емоції, сприйняття, пам’ять та інші когнітивні функції об’єднані в комплекс, який визначає специфіку людської поведінки та мислення. Модель враховує, що на перебіг психічних процесів впливає не лише індивідуальний досвід, а й універсальні символи та архетипи, які існують у колективному несвідомому, котре поділяють усі люди. Завдяки інтеграції різних аспектів розумової діяльності індивіди розвивають вищий ступінь самосвідомості, що суттєво підвищує ефективність когнітивної обробки даних.

A tanulmánya kognitív nyelvészetben az elmúlt évtizedekben a keretmodell (a mentális tereket strukturáló kognitív modell), a nyelvi hálózatok, sémák, prototípusok és gestaltokalapján használt fogalmi modellezés problémáira fókuszál. A kognitív névtan területén Olena Selivanova ukrán kutató egy új típusú fogalmi modellt javasolt, ami mentális-pszichonetikaikomplexumként (MPC) vagy más szóval több szubsztrátumból álló tudásegységként ismert, amely a verbális jelek belső programozásának motivációs alapját írja le. A mentális-pszichonetikai komplexum modelljét különbözőiskolák képviselői tesztelték eltérőnyelvek alanyeseti osztályain, valamint az ukrán nyelv és az irodalmi szintaxis frazeológiai egységeinek nominatívés kognitív jellegének elemzése során. A különféle jelek fogalmi elemzése a mentális-pszichonetikaikomplex modell segítségével lehetővé tette a motiváció problémájának új megközelítését, egy új tipológiakidolgozását, a nem-propozíciós (metaforikus) szintaktikai struktúrák nem-lineáris pozíciósémáinak kidolgozását. A „pszichonetika” kifejezést először a japán futuristák használták egy poszt-információs társadalom leírására, amelyben a hatékony adatfeldolgozási műveleteket többre értékelik, mint az adatgyűjtést. A fogalmak modellezésének pszichonetikus megközelítése magában foglalja a megismerés és a fogalmak manipulációja problémájának tágabb megközelítését. A modell a tudatos és tudattalan mentális folyamatok interakcióját fedi le. Az MPC célja, hogy a koncepciót több egymást átfedő és kölcsönhatásban lévő rétegből és síkból álló dinamikus struktúraként jelenítse meg. A tudat különböző aspektusai, mint például az intelligencia, az érzelmek, az észlelés, az emlékezet és más kognitív funkciók, olyan komplexumot alkotnak, amely meghatározza az emberi viselkedés és gondolkodás sajátosságait. A modell figyelembe veszi, hogy a mentális folyamatok lefolyását nemcsak az egyéni tapasztalat befolyásolja, hanem a kollektív tudattalanban létező univerzális szimbólumok és archetípusok is, amelyekenminden ember osztozik. A mentális tevékenység különböző aspektusaiintegrálásának köszönhetően az egyénekben magasabb fokú öntudat alakul ki, ami jelentősen növeli a kognitív adatfeldolgozás hatékonyságát.
Ментально-психонетичний комплекс як цілісна концептуальна модель
A mentális-pszichonetikai komplexum, mint integrált fogalmi modell
https://aab-philologica.kmf.uz.ua/aabp/issue/view/6/11
Keywords: conceptual model; frame; scheme; prototype; gestalt; psychonetics; mental-psychonetic complex; cognitive onomasiology